2010
DOI: 10.1007/s12182-010-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of CO2 sequestration in saline aquifers

Abstract: Storage of CO 2 in saline aquifers is a viable option for reducing the amount of CO 2 released to the atmosphere. This paper provides an overall review of CO 2 sequestration in saline aquifers. First, the principles of CO 2 sequestration are presented, including CO 2 phase behavior, CO 2 -water-rock interaction, and CO 2 trapping mechanisms. Then storage capacity and CO 2 injectivity are discussed as the main determinants of the storage potential of saline aquifers. Next, a site section process is addressed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 34 publications
1
61
0
1
Order By: Relevance
“…This process is typically known as mineral trapping and is considered to be a permanent form of CO 2 storage (Eke et al, 2011;Gaus et al, 2008;Liu and Maroto-Valer, 2011). More details regarding the CO 2 trapping mechanisms and numerical studies performed to understand the flow behavior of CO 2 in saline reservoirs due to different trapping mechanisms can be found in the literature (Bachu et al, 2007;Dilmore et al, 2008;Doughty, 2010;Fang et al, 2010;Gaus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is typically known as mineral trapping and is considered to be a permanent form of CO 2 storage (Eke et al, 2011;Gaus et al, 2008;Liu and Maroto-Valer, 2011). More details regarding the CO 2 trapping mechanisms and numerical studies performed to understand the flow behavior of CO 2 in saline reservoirs due to different trapping mechanisms can be found in the literature (Bachu et al, 2007;Dilmore et al, 2008;Doughty, 2010;Fang et al, 2010;Gaus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Geochemical reactions depend on several factors such as reservoir temperature, pressure, brine salinity, rock mineralogy, fluid injection rates, and time-scale of geological storage (Fang et al, 2010;van der Meer, 2005). In addition to the potential geomechanical risks associated with CO 2 injection that are discussed later in this section, it has been reported that chemical interactions of CO 2 -enriched brine with caprock minerals at the reservoir and caprock interface in the long-term might reduce rock strength, increase damage risks, and alter the flow properties of the caprock layer (Hangx et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…It involves burning coal in nearly pure oxygen. The main advantage of the oxy-fuel CO 2 capture technique is that the flue gas is available at a high CO 2 concentration of approximately 75.7 mol%, thereby reducing compression costs and facilitating efficient CO 2 removal [90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]. Although this technology appears promising if implemented for CO 2 capture in power plants, its possibility of implementation in the South African coal-fired power plants is quite slim because burning coal in pure oxygen instead of air on a large scale is very expensive.…”
Section: Oxy-fuelmentioning
confidence: 99%
“…One specific area of uncertainty relates to chemical interactions between injected CO2 and the reservoir fluids and rocks. In particular, dissolution of carbon dioxide in the reservoir brines gives rise to an acidic solution that may react with the rocks, especially when these contain carbonate minerals, with consequent changes in the porosity and permeability of the formation (2). In order to quantify such changes, it is necessary to have a fundamental quantitative understanding of the kinetics of mineral dissolution under realistic conditions of temperature, pressure and brine salinity.…”
Section: Introductionmentioning
confidence: 99%